Green Stink Bug, Acrosternum hilare (Say) (Insecta: Hemiptera: Pentatomidae) - Celina Gomez; Russell F. Mizell, III (EDIS, 2009)
EENY-431, a 5-page illustrated fact sheet by Celina Gomez and Russell F. Mizell III, is part of the Featured Creatures collection. It describes this commonly encountered pest of seeds, grain, nuts, and fruit — its distribution, description, life cycle and biology, hosts, damage, and management. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.